Valuation of PT Bank Tabungan Negara(Persero) TBK for Acquistion - Zuhrah, Fatimah Nur; Aliludin, Arson (Journal of Business and Management, 2014)
The purpose of this final project is to estimate the company value of PT Bank Tabungan Negara (Persero) Tbk or BTN as short, which is an Indonesian government-owned Bank in the form of a limited liability company and is engaged in the country’s mortgage loans sector, housing, banking financial services and Islamic banking. Its vision is to be the leading bank in housing finance in Indonesia. At the beginning of February 2014 there was an issue that PT Bank Tabungan Negara (Persero) Tbk or BTN will be acquired. Many banks were deemed to acquire BTN, but Bank Mandiri shows the most interest. Although the plans of acquiring BTN by Bank Mandiri were recently informed to have failed, Bank Mandiri claimed to still hold interest to acquire BTN and that the acquisition is highly possible even if it doesn’t happen in year 2014. In 2013, BTN was reviewed to have shown good performance in the business, but unexpectedly news about BTN going to be acquisitioned arise. Some viewed that the acquisition is not necessary. Up until now there are no banks that have a good position like BTN who focuses well on housing finance for the middle to low class market. The process of acquisition by another bank with a different business focus would make BTN lose its core focus; as a fact BTN now controls nearly 98% lower intermediate housing market. Therefore, the purpose of this final project is to examine the company value of BTN assuming it will be acquisitioned. The author will use valuation using numbers from BTN’s financial report and a review of its financial performance from year 2009 to 2013 using the valuation principles and methods specifically for valuing Banks which are: dividend discount model, cash flow to equity model, excess return model and relative valuation model. The values of equity per share generated from all four models respectively are Rp 823, Rp 1,489, Rp 857, Rp 869 compared to the actual market value per share of BTN by the end of year 2013 of Rp 870. Seeing that in actual BTN is currently performing well in the stock exchange, there is no need for an acquisition. Merely based on the calculations in this research, BTN is actually worth below its market value which is an advantage for the acquirer.